Analysis of Distance Relay Coordination Setting in 150 kV Transmission Line Protection System PLTMG BAUBAU Substation - BAUBAU Substation - RAHA Substation - Muhammad Nailul Ulum; Sukarno Budi Utomo (Eduvest - Journal of Universal Studies, 2026)
The electric power transmission system requires a reliable protection mechanism to ensure continuity and dependability, particularly in 150 kV transmission lines. One of the key protection devices used is the distance relay, which detects and isolates faults based on impedance measurements. This study was initiated following a fault on the PLTMG Baubau–Raha transmission segment, which caused a power outage of 8.7 MW lasting 2 hours and 23 minutes. The objective of this research is to analyze the coordination settings of distance relays and evaluate the performance of the teleprotection system in responding to disturbances, as well as to estimate energy loss and its economic impact. The methodology includes collecting primary data from PT PLN (Persero) and simulating fault conditions based on the actual relay settings installed at three substations: PLTMG Baubau, Baubau, and Raha. The analysis revealed that the relay zone settings and timing delays were functioning correctly, and the Permissive Underreach Transfer Trip (PUTT) teleprotection scheme successfully accelerated fault isolation in a selective manner. Simulations also confirmed that the system accurately identified fault locations based on impedance values detected by the relays. Additionally, calculations showed a total energy loss of 20,732.1 kWh, equivalent to IDR 29,939,622.4. This study emphasizes the importance of proper relay coordination and teleprotection systems in enhancing the reliability of power transmission networks.